Toru Takemitsu : a response to his compositional world through theory and practice - Lim, Mona Lay Im. (2009)
This M.A. dissertation is a continuation of my research on the late composer Toru Takemitsu (1930 - 1996). This piece of study is focused more on his compositional techniques and the styles characteristic of the composer, especially his concept of "ma" which embodies the idea of spatial awareness in Nature. This concept heavily influenced him at the point of his life when he consciously turned back to his traditional roots as a Japanese and began to use traditional Japanese instruments, namely the shakuhachi and the biwa in his compositions. Two of Takemitsu's works have been selected here for a more detailed study; the first is Piano Distance (1961), a relatively early piano work, and the second work is November Steps (1967), a work for solo shakuhachi, biwa and chamber orchestra.